Pengaruh Kesadaran, Sosialisasi Perpajakan, Kualitas Pelayanan Fiskus dan Penerapan e-filing Terhadap Kepatuhan WPOP - Nova Arianto Toldo Pratama; Susanti Susanti (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2021)
Tax revenue is the main source of revenue from APBN. Seeing the importance of taxes in advancing and developing the country, it is natural that the Indonesian government targets taxpayer compliance to continue to increase every year, especially income tax. However, when viewed from the percentage of individual taxpayer compliance (WPOP) KPP Pratama Surabaya Gubeng, each year has decreased in the last four years. This study aims to test whether awareness, socialization of taxation, quality of tax service services, and the application of e-filing have an effect on WPOP compliance. The method used is a quantitative method with a sample of 100 WPOP KPP Pratama Surabaya Gubeng. Collecting data using a questionnaire. Analysis of the data used, namely multiple linear regression. The results of this study simultaneously all independent variables together affect WPOP compliance. While partially, awareness, socialization of taxation, and the application of e-filing affect WPOP compliance, but the quality of tax services does not affect WPOP compliance.